Likhamon 2023 Book of Abstracts - Research, Development and Innovation Office (Romblon State University Research Journal, 2023)
In line with the university's vision of becoming a research-based academic institution, a key priority is fostering research, development, and innovation skills. This commitment extends to all university community members, including the students. The Likhamon 2023: Student Research Congress was organized as a testament to this dedication. This is an energetic and dynamic platform where young minds converge to participate in presenting the results of their respective research. By engaging in student congress, students gain invaluable experiences in developing critical thinking and public speaking while learning the art of diplomacy, collaboration, and compromise. Moreover, it nurtures a sense of civic responsibility and empowers students to actively contribute to shaping their school community, fostering inclusivity, and tackling social issues. Through student congress, aspiring leaders emerge, ideas flourish, and enduring impacts are realized, creating a nurturing atmosphere that cultivates well-informed and engaged citizens of the future.